KUALITAS PELAYANAN INSTALASI GAWAT DARURAT DI RUMAH SAKIT UMUM PUSAT PROF. dr. R. D. KANDOU MANADO - Debora Marlien Mamengko; Femmy ., Tasik; Joyce J. Rares (AGRI-SOSIOEKONOMI, 2021)
Service to the community (patients) is a job that specializes in efforts to patients with work demands that depend on certain characteristics in carrying out their work, namely, task characteristics and materials such as (equipment, speed, alertness), organizational characteristics, namely working hours / shift. work and work environment characteristics such as friends, duties, temperature, noise, lighting, socio-culture. This study aims to analyze the quality of services for the Emergency Room in RSUP Prof. dr. R. D. Kandou Manado. The research method used a qualitative descriptive design. A sample of 10 informants was taken by purposive sampling with a research focus on reliability, responsivisness, assurance, empathy and tangibles (physical products) by collecting data using interviews, observation and documentation analyzed by reducing data, presenting data and drawing conclusions. The results of the research show that the quality of services for the Emergency Room in the General Hospital Prof. dr. R. D. Kandou Manado still needs to be improved, especially on responsiveness and tangibility, namely responsiveness and repair and provision of physical equipment which is still considered insufficient.